Medicine's #MeToo moment: five minutes with . . . Becky Cox and Chelcie Jewitt. (19th July 2022) - Politis, Marina
Abstract : The co-founders of the Surviving in Scrubs campaign discuss their work to expose and highlight cases of sexism, sexual harassment, and sexual assault in healthcare